The Impact of Nurses’ Knowledge and Self-Efficacy on Quality of Life and Symptom Burden for Patients with Gastric Cancer Receiving Palliative Care in Jordan: A Review of Literature - Ass’ad, Nizar Adnan Rfefan (Journal of medical and pharmaceutical sciences, 2024)
Gastric cancer is one of the most prevalent and fatal cancers that has been reported around the world. Numerous studies reported poor and limited nurses’ knowledge of palliative care services. Despite the numerous measures Jordan has taken to improve the palliative care concept, Jordan still confronts numerous difficulties and issues. This review of the literature on nurses’ self-efficacy and knowledge while providing palliative care to patients with gastric cancer and nurses’ perceptions of the barriers and needs towards palliative care services. The literature suggests that nurses have poor self-efficacy and knowledge concerning managing cancer symptoms, enhancement of quality of life, and therapy management plans (like opioids) for patients in palliative care units. Unfortunately, few studies have focused on palliative care in Jordan. This suggests a significant gap in literature studies on palliative care in Jordan.